Physical and Chemical Characteristics of Feed Coal and its by-products from a Brazilian Thermoelectric Power Plant - Juliana de Carvalho Izidoro; Caio Miranda; Davi Castanho; Carlos Rossati; Felipe Campello; Sabine Guilhen; Denise Fungaro; Shaobin Wang (Journal of Applied Materials and Technology, 2019)
In this study, feed coal (FC) from the Figueira Thermoelectric Power Plant (FTPP), located in the state of Paraná (PR), Brazil was characterized by X-ray fluorescence (XRF), X-ray diffractometry (XRD), infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), particle size distribution analysis by laser diffraction, loss of ignition (LOI), total carbon content (TC), pH and conductivity. FC-derived by-products (CCBs) collected at the FTPP were: bottom ash (BA), fly ash from cyclone filter (CA) and fly ash from bag filter (FA). In addition to the techniques used for feed coal characterization, CCBs were also characterized by total surface area (by using BET method), external surface area (by using laser diffraction), cation exchange capacity (CEC), bulk density, besides leaching and solubilization tests. FC sample contains 72.2% of volatile material, of which 55.3% is total carbon content. LOI, FTIR, TGA and TC analyzes corroborated with these results. The main crystalline phases in the FC sample were found to be quartz, kaolinite and pyrite. The elements As, Cr, Ni and Pb were encountered in the FC sample, indicating that the use of FTPP feed coal should be monitored due to the toxic potential of these elements. The three coal ashes were classified as class F according to ASTM and presented similar chemical composition, with total content of the main oxides (SiO2, Al2O3 and Fe2O3) above 72%. Ashes enrichment factor analysis (EF) showed that As, Zn and Pb concentrate mainly in fly ash from bag filter (FA), whereas the elements K and Mg presented higher enrichment in the bottom ash (BA) . All ashes presented quartz, mullite and magnetite as crystalline phases, as well as the same functional groups, related to the presence of humidity, organic matter and Si and Al compounds. XRD, XRF, TGA, FTIR, LOI and TC techniques were correlated and confirmed the obtained results. Total and external surface area values of CCBs were related to the total carbon content (TC), as well as to the results of particle size distribution and the scanning electron micrographs of the samples. On the other hand the CEC of the ashes showed relation with the particle size distribution and with the external surface area. Leaching and solubilization tests of CCBs showed that FA sample was considered hazardous and classified as class I waste, while CA and BA samples were considered non-hazardous and non-inert wastes and classified as class II-A. FA sample from Figueira power plant must be discarded only after treatment or a stringent disposal criterion must be followed to avoid contamination on site. In this work, feed coal sample was also compared to the CCBs samples generated from it. The results showed the differences between fuel and products through the different characterization techniques. In addition to contributing to the understanding of the relationship between coal and its combustion products, this work can also help to reduce the environmental impacts caused by the CCBs disposal, as well as can also be used to compare the characteristics of CCBs from FTPP with the new wastes that will be generated by the same thermal power plant that will be soon modernized.